HEALTHY NUTRITION AS A KEY TO A BETTER LIFE - Nilufar Tuychiyeva Mahsutjanovna (Sciental Journals Publishing, 2025)
This article explores the ethical dimensions of food consumption in Islam, focusing on the prophetic teachings that emphasize moderation, communal eating, and the avoidance of waste. Drawing on hadith literature and contemporary dietary concerns, the discussion highlights how the Islamic tradition offers a holistic framework for healthy and socially conscious nutrition practices.
Keywords: Healthy eating, Prophetic medicine, Islamic dietary ethics, Hadith and health, Preventive health in Islam, Moderate consumption, Fasting and well-being, Food etiquette in Islam, Physical health, Avoiding wastefulness.